Comparison of Radiographic and Clinical Outcomes of First Tarsometatarsal Arthrodesis with the Lapiplasty System vs Cross-Screw Fixation. Issue 4 (November 2022) - Fuller, Robert; Fletcher, Amanda N.; Rajan, Lavan; Zhu, Jiaqi; Easley, Mark E.; Nunley, James A.; Cody, Elizabeth
Category: Midfoot/Forefoot; Bunion Introduction/Purpose: Hallux valgus (HV) is recognized as a triplanar deformity comprising axial abduction, sagittal hypermobility, and coronal pronation of the first metatarsal. A first tarsometatarsal (TMT) arthrodesis may be used to address all three planes of deformity. The Lapiplasty system (Treace Medical Concepts, Inc., Ponte Vedra, FL) was developed to reproducibly address triplanar deformity. However, the Lapiplasty system is costlier than other fixation constructs. Because healthcare is increasingly value-focused, we sought to determine if the more expensive Lapiplasty system improved radiographic outcomes or decreased complication rates over standard cross-screw fixation. We hypothesized that HV patients undergoing first TMT arthrodesis with the Lapiplasty system would have equivalent radiographic correction and similar complication rates when compared to patients treated with cross-screw fixation. Methods: In this multi-center, IRB-approved retrospective study, consecutive series of patients who underwent 1st TMT arthrodesis for HV, either with cross-screw fixation at Institution A, or Lapiplasty at Institution B, were identified by registry search. Inclusion criteria included age over 18 and preoperative and minimum 6-month postoperative weight-bearing AP and lateral radiographs. Exclusion criteria included primary conditions other than hallux valgus and previous first ray surgeries or ipsilateral arthrodeses. Hallux valgus angle (HVA), intermetatarsal angle (IMA), and tibial sesamoid position (TSP) were measured preoperatively and at final follow-up, and clinic notes were reviewed to identify complications and reoperations. To compare cohorts, Mann-Whitney U tests and Fisher's Exact tests were applied for continuous and discrete variables, respectively. To examine preoperative-postoperative changes, Wilcoxon signed rank tests were used. Multivariable regressions tested the effect of fixation constructs on postoperative radiographic parameters, adjusted for preoperative radiographic measurements, age, sex, and BMI. Results: 65 patients were included in each group, with 121 (93.8%) female patients, mean (SD) age 54.7 (14.8), BMI 25.8 (5.2), and radiographic follow-up time 8.9 (6.7) months. The Lapiplasty cohort had greater BMI (26.8 vs. 24.7, P = .048), and there were no significant differences between groups in age, sex distribution, and radiographic follow-up time. Radiographic measurement data is displayed in Table 1. After adjusting for age, sex, BMI, preoperative HVA, and preoperative IMA, fixation with Lapiplasty was significantly associated with lower postoperative IMA (b=-2.03, 95% CI = [-2.78, -1.37], P < .001) and lower postoperative HVA (b= -7.48; 95% CI = [-9.69, -5.26]; P < .001), but not postoperative sesamoid position. There were no significant differences between cohorts in the incidence of complications or reoperations. Conclusion: We found that use of the Lapiplasty system was associated with better radiographic hallux valgus correction, as evidenced by lower postoperative HVAs and IMAs, compared to standard technique with crossing screws. The clinical significance of these findings is unclear, as complication and reoperation rates were similar between groups. Future research assessing longer- term outcomes, patient-reported outcome data, and cost-benefit analysis will be necessary to further compare techniques and fixation systems.